SABER Tools as a Framework for Education System Assessment - World Bank (World Bank, Washington, DC, 2017)
The World Bank Group’s Systems Approach for Better Education Results (SABER) initiative produces data on education system policies and institutions, analyzes and evaluates their quality, and provides decision makers and stakeholders with an assessment that fosters structured and informed policy dialogue on how to most effectively strengthen education systems. During its tenure, SABER has grown rapidly to become a key component in the design of education programming across the globe, providing countries with quality data and information. By generating a broader knowledge base on education systems worldwide, these tools are helping reform education at the country level while also building a high-quality knowledge base for education reforms at the global level. SABER materials, including framework and other background documents, user manuals, questionnaires, rubrics, as well as country reports and analytical papers, are made publicly available to encourage widespread use of SABER tools and publications, helping to strengthen education policy development and reform. The openness of SABER methodology and data also enables stakeholders to adapt SABER tools in a way that is relevant to their individual needs. The World Bank Group’s education team in China, in collaboration with researchers at the Shanghai Normal University, recently published a report ‘how Shanghai does it: insights and lessons from the highest-ranking education system in the world’, which uses SABER as a framework to organize and benchmark education policies across several areas of the education system. The findings of the report and the related analyses were highlighted during the global conference on equity and excellence in basic education in Shanghai in May 2016.